Revisiting differential grading standards anno 2014: an exploration in Dutch higher education. Issue 4 (19th May 2017) - Godor, Brian P.
Abstract : The role that teachers have in assessing student coursework is crucial. Their 'determination' that a particular piece of student's work is 'acceptable' has many serious consequences. With a lack of debate surrounding assessment, practices may become mired in conventions and disconnected from issues such as knowledge, power and social organisation. They may also become divergent between faculties, with majors with academically stronger students grading more stringently and those with academically weaker students grading less stringently. In order to test for potential differential grading standards due to adaption-level, this study examines the relationship of pre-entry secondary school grades (English, Dutch and Mathematics) to first-year average grades in 11 faculties ( n  = 3080). The results presented demonstrate the presence of differential grading standards among the different faculties within this population.